Does delay in initiation of intravenous antibiotics correlate with wound infections in children with open fractures? - Anil Kumar Chintada; Anil Kumar Nathi (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2019)
Introduction: One of the common complications of open fractures is an infection which may be dependent on the time of administration of antibiotics. The study aimed to determine the prevalence of wound infection due to the delay in the interval between the initiation of intravenous (IV) antibiotics and time of paediatrics open injury.Materials and Methods: Retrospective observational study included paediatrics patients (0 to 16 years) with open fractures. A retrospective chart review was performed to identify patients with open fracture, who were treated between May 2012 and October 2013 at the tertiary care centre. The time between the injury and the first dose of intravenous antibiotic was calculated from transfer and hospital records. Fracture groups were stratified according to the severity of soft-tissue damage as determined with use of the Gustilo- Anderson system for the classification of open fractures.Results: Sixty patients with 84 open fractures were included in this study. Majority of 31.58% of participants had type III B Gustilo - Anderson fracture type. The proportion of grade IIIA, I, III C and II fracture was 29.82%, 21.05%, 14.04% and 3.51% respectively. 43 (71.6%) received IV antibiotics within 6 hours of injury of which eight had documented wound infections. Of the 17 (28%) patients who received IV antibiotics after 6 hours, 7 (41%) were diagnosed with wound infections. The incidence of infection was high in higher grades of Gustilo- Anderson opens injuries.Conclusion: The immediate administration of appropriate antibiotics on presentation is crucial to minimise the risk of infection in children.